Penerapan Atraumatik Care: Audiovisual terhadap Penurunan Kecemasan pada Anak Usia Prasekolah - Selvia Novitasari; Weti Weti; Ferasinta Ferasinta; Nopia Wati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of applying atraumatic care with audiovisuals to reduce or minimize the anxiety of hospitalized children during the COVID-19 pandemic at Harapan and Doa Hospital, Bengkulu City. This research method is quantitative research with a quasi-experimental design. The results showed that the difference in the average decrease in anxiety frequency before and after the intervention was 2,500 with a standard deviation of 1,761, the value of 95% CI (0,652 - 4,348), p-value obtained 0.018 < = 0.05. In conclusion, there is a significant effect on the level of anxiety of preschoolers before and after the audiovisual intervention at Harapan and Doa Hospital Bengkulu City. Keywords: Children, Audiovisual, Anxiety